The brand crisis and communication strategies - Černikovaitė, Miglė Eleonora Eleonora (Information & Media, 2018)
[only abstract and keywords in English; full article, abstract and keywords in Lithuanian]This article analyzes the problem of the brand crisis in contemporary business. The brand crisis is said to be a public and press-related event that is most commonly caused by consumers voicing their experiences regarding unsafe, poor-quality or even harmful products. It is noted that the crisis can affect the entire product category of the company or only a certain group of goods and damage the everyday business, thus endangering future activities, leading to material losses and damaging other property – the company’s image and reputation. The aim of this article is to analyze the causes of Lithuanian brand crises and to identify the strategies of brand communication crises that would allow the companies to manage their images in crisis situations. Based on a quantitative analysis of the content analysis, separate examples of Lithuanian brand crises, their social responsibility issues and risk management, as well as the brand management issues, were analyzed. It discusses how to prepare a communication strategy for managing a brand crisis that would reduce reputational risk and anticipate an action plan to “exit” from the crisis with the smallest business losses.The results of the survey showed that the reputation of the crisis does not differ between the less or more commonly chosen brands, the awareness of the crisis did not differ between the most commonly chosen Lithuanian brands and those that are more likely to pick up their competitors’ goods. This shows that manufacturers and/or vendors must take care to communicate not only with their loyal customers and provide and explanation of how to deal with a crisis in order to minimize damages, but that manufacturers and/or vendors must also ensure that this message reaches all potential users of the product category.Often, the authors point out two more components of the impact of the crisis, namely the perception of reliability and the perceived risk and the importance of brand loyalty. Crisis communication strategies suggest that these variables should be included, as this can help in identifying what exactly affects the perceptions and behavioral changes of consumers after a brand crisis.
Keywords: brand crisis, social responsibility, reputation and image, communication strategy